New remains of Prochelidella in the Anacleto Formation (Campanian levels) of Neuquén basin, Patagonia, Argentina - Maniel, Ignacio Jorge (2021)
The new turtle remains presented here were recovered from the Anacleto Formation (Campanian) exposed in the Aguada Grande site. This area is located 10 km south of Rincón de Los Sauces city, inthe north of the province of Neuquén, Patagonia, Argentina. The specimen (MAU-Pv-AG-452)consists of a partially preserved skull, carapace remains, an almost complete plastron, and a leftilium. The new specimen is assigned to Pleurodira because its ilium is sutured to the carapace. Both Parietals, the posterior part of frontals and post orbitals, the dorsal region of the supraoccipital, both pterygoids, the basisphenoid, and part of the prootics are recognized in the skull. The carapace remains are represented by a left first costal bone in articulation with a peripheral bone, a left paired costal bone, and another fragmented coastal. The plastron is represented by both epiplastra, theen plastron, left hyoplastron, both hypoplastra, and the left xiphiplastron. The skull shows somecharacters that allow its referral to Prochelidella spp. (e.g., a developed retropterygoid foramen, and a big muscle attachment area over the basisphenoid). The visceral view of the first costal bone exhibitslong auxiliary buttresses that extend 2/3 of the costal width. This condition is also observed in the costal bone of Prochelidella buitreraensis from the Candeleros Formation (Cenomanian). The scutepattern observed in the anterior lobe of the plastron shows a large gular that extends along theentoplastral length and small extragulars over the epiplastra. In contrast, on the scheme observed inProchelidella cerrobarcinae and Prochelidella portezuelae, the gular does not extend beyond the first third of the entoplastron. The material recovered from the Anacleto Formation represents the most complete specimen outside the Prochelidella peak of diversity range (Albian Cenomanian) and the second skull recognized in this genus